On the minimisation of resource utilisation for cost reduction in space division multiplexing based elastic optical networks. Issue 1 (7th April 2022) - Iyer, Sridhar
In the current work, for a Space Division Multiplexing (SDM) based Elastic Optical Network (EON) (SDM-b-EON), a routing, modulation format, spatial granularity (SpGl), and spectrum assignment (RMFSpGlSA) problem is formulated with an aim to minimise the overall network cost by reducing the resource usage. RMFSpGlSA is formulated as a joint integer linear program (J-ILP) model (J-ILP-RMFSpGlSA), and the ILP-RMFSpGl+SA model which successively solves the RMFSpGl and the SA problems. Extensive simulations are conducted to evaluate the performances of the two formulated ILP models with an aim to find the 'best' SpGl value under various conditions. The obtained results demonstrate that fine values of SpGl are mostly chosen with the widening of guardband width values, and with an increase in the mean bit-rate values of demands, a coarse value of SpGl is mostly chosen. Finally, all the results demonstrate that ILP-RMFSpGl+SA obtains similar performance when compared to J-ILP-RMFSpGlSA simultaneously requiring much lesser execution times.